Are ENT1/ENT1, NOTCH3, and miR-21 Reliable Prognostic Biomarkers in Patients with Resected Pancreatic Adenocarcinoma Treated with Adjuvant Gemcitabine Monotherapy? - Jiraskova, Lucie; Ryska, Ales; Duintjer Tebbens, Erik Jurjen; Hornychova, Helena; Cecka, Filip; Staud, Frantisek; Cerveny, Lukas (Cancers, 2019)
Evidence on equilibrative nucleoside transporter 1 (ENT1) and microRNA-21 (miR‑21) is not yet sufficiently convincing to consider them as prognostic biomarkers for patients with pancreatic ductal adenocarcinoma (PDAC). Here, we investigated the prognostic value of ENT1/ENT1, miR-21, and neurogenic locus homolog protein 3 gene (NOTCH3) in a well-defined cohort of resected patients treated with adjuvant gemcitabine chemotherapy (n = 69). Using a combination of gene expression quantification in microdissected tissue, immunohistochemistry, and univariate/multivariate statistical analyses we did not confirm association of ENT1/ENT1 and NOTCH3 with improved disease-specific survival (DSS). Low miR-21 was associated with longer DSS in patients with negative regional lymph nodes or primary tumor at stage 1 and 2. In addition, downregulation of ENT1 was observed in PDAC of patients with high ENT1 expression in normal pancreas, whereas NOTCH3 was upregulated in PDAC of patients with low NOTCH3 levels in normal pancreas. Tumor miR‑21 was upregulated irrespective of its expression in normal pancreas. Our data confirmed that patient stratification based on expression of ENT1/ENT1 or miR‑21 is not ready to be implemented into clinical decision-making processes. We also conclude that occurrence of ENT1 and NOTCH3 deregulation in PDAC is dependent on their expression in normal pancreas.